An analysis on damages for loss of future earnings under section 28A(2)(c) of civil law (Amendment) Act 1984 / Nurazreen Ajar … [et al.] - Ajar, Nurazreen; Hussin, Nur Diyana; Roslan, Noor Ain; Anuar, Nur Dalila Najwa (2014)
This dissertation is regarding the law of personal injury which is governed under Section 28A of the Civil Law Act 1956. People are prone to accidents and in a situation where one suffered injury due to the negligence of another, the victim may bring in action in court. The law of personal injury protects those people who sustained injuries to their bodies due to the act of another. However, the current law in Malaysia provide strict requirement in a claim for compensation especially in the matter of loss of future earnings. As a result, many victims are unable to claim for loss of future earnings due to failure to comply with the restrictions made by the Parliament. The current law can be regarded as too rigid and failed to provide justice for the claimants. This dissertation therefore discuss the position of the law before amendments, the requirements needed in a claim for loss of future earnings, the loopholes in the current law and recommendations for a better law to assists victims who are wronged due to the harshness of the law provided with a view to reform the current law and alleviate its austerity.